Créditos - FALE - UFMG, Pós-Lit (Em Tese, 2014)
EDITORES EM TESE Cleber Araújo Cabral Felipe Oliveira de Paula Gustavo Cerqueira Guimarães João Alves Rocha Neto Josué Borges de Araújo Godinho Julia Gomes Panadés Rafael Otávio Fares